Komodifikasi Perempuan pada Iklan Pond's Perfecting Cream Edisi WOW! Featuring Maudy Ayunda (2019) (Faculty of Communications Science, Dr. Soetomo University, 2020)
This study aims to determine the practice of commodification of women by exploring the meaning of verbal and nonverbal symbols or language in the ad edition of Pond's WOW! This study also wanted to find out the meaning of reality, the meaning of representation, and the meaning of ideology in the ad edition of Pond's WOW! Featuring Maudy Ayunda (2019). The commodification of women in this advertisement shows that the practice of femvertising (women advertising) places women as objects. Instead of empowering women, the practice of femvertising makes women increasingly marginalized in media texts. Women are imaged with a variety, only on matters of dress style and skin color, not on big things like hard work, independence, and determination. This research considers that advertising practices are not a strategy to empower women by building constructive messages. The practice of femvertising is just a cover for capitalism to wrap advertisements with a certain appeal so that women pay attention. Women's attention to a product will leadto purchasing decisions, which in turn will bring benefits to the product. Keywords: Commodification; Women in Advertising; Semiotics; John Fiske.